IMPLEMENTASI SMART MINI MARKET SEBAGAI TEACHING FACTORY UNTUK MENDUKUNG LINK AND MATCH PENDIDIKAN VOKASI DENGAN DUNIA INDUSTRI DI SMK KARYA ABADI - Irawati, Indrarini Dyah; Ramadan, Dadan Nur; Supriyadi, Didi (Jurnal Abdi Insani, 2025)
SMK Karya Abadi Sumedang has limitations in terms of Teaching Factory (TeFa) facilities, particularly in the field of Retail Business, as a result of which students do not have the opportunity to gain direct experience in modern business management. Telkom University is collaborating with industry partner PT Sinai Teknologi Abadi to meet this need through the Smart Mini Market: Qmart program as part of its community service program. The goal is to improve student competence through the creation of Teaching Factory facilities for practical learning. The QMart application was developed as a Point of Sales (POS) system, along with modules and video tutorials as operational guides, as well as mini market facilities for practical training, and the implementation of QMart Operational Workshops. All of these stages are part of the implementation process. The results of the activity show that participants gained a better understanding of stock management, using digital cashier systems, and creating product marketing strategies. Teachers benefited from the integration of the Teaching Factory into the curriculum, while the school gained an independent business that can provide financial assistance. Additionally, the results of the questionnaire given to workshop participants indicate that this program meets their needs and is able to improve their understanding of mini market operations, particularly the QMART application. Participants' average initial scores increased from the moderate category (2.27–3.14) to the high category (4.03–4.68) after the workshop. The aspect of confidence in using the QMart application and encouragement for digital entrepreneurship showed the most significant improvement. It has been proven that the QMart implementation program is appropriate, efficient, and has a positive impact on improving the quality of vocational education in the scope of work practices through the Teaching Factory. This program also supports the link and match between vocational education and industry needs as well as the empowerment of the surrounding community.